The Utility of a Collective Identity Construct to Explore the Influence of Farming Identity on Natural Resource Management. Issue 5 (3rd May 2016) - Groth, Theresa M.; Curtis, Allan; Toman, Eric; Mendham, Emily
ABSTRACT: Change in the occupational identity of rural residents is expected to influence natural resource management (NRM). Self-declaration is the most common way of assessing occupational identity (OI) but is largely atheoretical. Researchers have suggested that the collective identity construct (CIC) might provide a theoretically derived and reliable measure of OI. In this article we reflect on the first attempt to evaluate the application of the CIC in the NRM context. Rural landholders in Australia and the United States were interviewed to assess whether the CIC would distinguish between full-time farmers, part-time farmers, and nonfarmers, and to determine whether there were opportunities to refine the lengthy list of CIC dimensions and elements for future studies. This research suggests the CIC will be an effective measure of OI in that differences between the landholder cohorts emerged for five of seven CIC dimensions. We conclude by suggesting how these dimensions might be operationalized in a survey.